Lectotipification of "Cistus laevipes" L. ("Cistaceae") - Ferrer-Gallego, P. Pablo; Laguna, Emilio (Botanica Complutensis, 2013)
The current information on basionyme of Fumana laevipes (L.) Spach, shows that this taxon is not typified. In this paper the original material enclosed in a herbarium sheet at UPS-BURSER is designated as lectotype.
Keywords: nomenclature; lectotype; Fumana laevipes; Cistaceae